Some Identities of Symmetry for the Generalized Bernoulli Numbers and Polynomials - Taekyun Kim; Seog-Hoon Rim; Byungje Lee (Abstract and Applied Analysis)
By the properties of p-adic invariant integral on ℤp, we establish various identities concerning the generalized Bernoulli numbers and polynomials. From the symmetric properties of p-adic invariant integral on ℤp, we give some interesting relationship between the power sums and the generalized Bernoulli polynomials.